2020
DOI: 10.3390/ani10020209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on the In Vitro Maturation of Porcine Oocytes, Development of Parthenogenetically Activated Embryos, and Expression of Genes Related to the Oocyte Developmental Capability

Abstract: Melatonin treatment can improve quality and in vitro development of porcine oocytes, but the mechanism of improving quality and developmental competence is not fully understood. In this study, porcine cumulus–oocyte complexes were cultured in TCM199 medium with non-treated (control), 10−5 M luzindole (melatonin receptor antagonist), 10−5 M melatonin, and melatonin + luzindole during in vitro maturation, and parthenogenetically activated (PA) embryos were treated with nothing (control), or 10−5 M melatonin. Cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 64 publications
5
22
0
Order By: Relevance
“…Moreover, the expression levels of GDF9 and BMP15, which are related to oocyte competence [47], were also significantly influenced in each experimental group. Various studies also suggested that melatonin is associated with ROS mechanisms in oocytes [48][49][50], and our results corroborated these findings. Additionally, we observed the negative effects of brusatol on GSH and ROS levels.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the expression levels of GDF9 and BMP15, which are related to oocyte competence [47], were also significantly influenced in each experimental group. Various studies also suggested that melatonin is associated with ROS mechanisms in oocytes [48][49][50], and our results corroborated these findings. Additionally, we observed the negative effects of brusatol on GSH and ROS levels.…”
Section: Discussionsupporting
confidence: 90%
“…In the recent study by our group, we found that melatonin concentration of 10 −5 M significantly improved the quality of mitochondria maturation in porcine oocyte as compared to the control group. However, these beneficial effects of melatonin could be blocked by 10 −5 M luzindole, which is a melatonin receptor antagonist (Yang et al, 2020). As per the previous report, the melatonin concentrations of 10 −3 -10 −11 M positively affects the porcine oocyte maturation, and 10 −9 M melatonin is the optimum concentration for porcine oocyte maturation in vitro (Shi et al, 2009).…”
Section: Discussionmentioning
confidence: 60%
“…In pigs, it has been reported that supplementation with different antioxidants, such as crocin 26 , sphingosine-1-phosphate 27 or melatonin 28 , during in vitro maturation culture improved the cleavage rates. Nevertheless, when supplementation was performed exclusively during embryo culture, the cleavage rate was not affected 9 , 11 .…”
Section: Discussionmentioning
confidence: 99%